Validity and reliability of the International Physical Activity Questionnaire (IPAQ) long-form in a subsample of female Mexican teachers - Catalina Medina; Adriana Monge; Edgar Denova-Gutiérrez; Ruy López-Ridaura; Simón Barquera; Isabelle Romieu; Martín Lajous (Instituto Nacional de Salud Pública, 2022)
Objective. To evaluate the test-retest reliability and validity of the long-form International Physical Activity Questionnaire (IPAQ-long form). Materials and methods. A subsample of 86 teachers underwent telephone interviews and clinic visits in Mexico City. Through 22 months, physical activity (PA) levels were obtained from accelerometers (months 6 and 22) and IPAQ long-form (months 1, 3, 6, 9 and 12). Minutes per week of moderate (MPA), walking (WPA), vigorous (VPA) and moderate-to-vigorous physical activity (MVPA) were calculated for each intensity and domain. Variables were logarithmically transformed. Intra-class and Pearson correlations were used to determine the relationship between instruments. Results. Test-retest reliability of the average IPAQs long-form varied across intensities and domains (ranged from r= 0.24 to r= 0.65). Minutes per week of VPA and MVPA accelerometer 1 (AC1) were fairly associated to International Physical Activity Questionnaire-long form 3 (IPAQ3) (r= 0.60 and r= 0.31, respectively) one week apart. Conclusions. IPAQ long-form is fairly reliable for MVPA and valid for assessing MVPA and VPA in a subsample of Mexican teachers.